Exploring Factors Impacting Oral Health Behavior in Children with Special Needs - Choirunnisa, Amalia; Pamungkasari, Eti Poncorini; Murti, Bhisma; Sumardiyono, Sumardiyono; Novika, Revi Gama Hatta (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Oral health is a reflection of general health. Children with disabilities are more prone to problems such as dental caries and periodontal disease compared to children in general due to various factors. Indonesia has 3.3% of children with disabilities aged 5 to 17 years old. Families, especially mothers, play a crucial role in maintaining the dental health of children with disabilities because they are responsible for meeting basic needs and oral hygiene. The Health Belief Model theory can be used to understand parental behavior related to the health of children's oral cavity. This study aims to examine the influence of factors in HBM theory on the oral health of children with special needs. Subjects and Method: This study uses a cross-sectional method conducted at Sukoharjo and B-C YPPALB Langenharjo schools for special needs children, Central Java, Indonesia. A total of 200 parents or guardians of children with disabilities were obtained by random sampling. The bound variable was in the form of oral health behavior while the independent variable was in the form of vulnerability perception, severity perception, benefit perception, obstacle perception, stimulus to act, and self-efficacy. The results of the study were analyzed using multiple linear regression. Results: Oral Health Behavior increases with increased perception of vulnerability (b= 0.11; 95% CI= 0.11 to 0.21; p= 0.030), perception of severity (b= 0.16; 95% CI= 0.17 to 0.30; p= 0.028), perception of benefit (b= 0.12; 95% CI= 0.16 to 0.22; p= 0.024), stimulus to act (b= 0.18; 95% CI= 0.11 to 0.35; p= 0.037), and self-efficacy (b= 0.18; 95% CI= 0.11 to 0.26; p=0.000) and decreases with increasing perception of barriers (b= -0.15; 95% CI= -0.20 to - 0.11; p=<0.000). Conclusion: Perception of vulnerability, perception of severity, perception of benefit, stimulus to act and self-efficacy increase oral health behavior and perception of obstacles decreases oral health behavior.